Argentine cinema and nation (2012)
This article analyzes the uses of space in the representationof Post-Dictatorial Nation in three argentine films,Tangos, el exilio de Gardel and Sur by Fernando Solanasand Un muro de silencio by Lita Stantic. The article developsdiegetic and extradiegetic conceptions of spaceas ways of naming the post dictatorial nation, in a kindof mourning that fulfills the emptiness between the pastand present and the nation that disappears with theviolence of dictatorial rule.